Inoculant-treated corn silages for growing cattle - Bolsen, K.; Kireh, B.; Laytimi, A.; Hoover, J.; Ilg, H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Whole-plant corn silages were treated with Ecosyl® in one trial and Biomate4ll or Silagest® in a second trial. In both trials, the silages were well preserved and moderately stable in air during the feed-out period. Inoculated silages had slightly lower ensiling temperatures than control silages. Laboratory silo results indicated that all silages fermented extremely fast, but inoculated silages did have slightly lower pH and higher lactic acid values during the first 4 days post-filling. Calves fed inoculated silage rations tended to gain faster and more efficiently than those fed control silages. Gain per ton of crop ensiled also favored the inoculated silages.
Keywords: Beef; Inoculant; Corn silages; Growing cattle